2023
DOI: 10.7554/elife.82593
|View full text |Cite
|
Sign up to set email alerts
|

Rapid protein stability prediction using deep learning representations

Abstract: Predicting the thermodynamic stability of proteins is a common and widely used step in protein engineering, and when elucidating the molecular mechanisms behind evolution and disease. Here, we present RaSP, a method for making rapid and accurate predictions of changes in protein stability by leveraging deep learning representations. RaSP performs on-par with biophysics-based methods and enables saturation mutagenesis stability predictions in less than a second per residue. We use RaSP to calculate ∼ 300 millio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 65 publications
1
27
0
Order By: Relevance
“…AlphaFold2 models were used for proteins or select residues in infrequent cases where they were not covered by experimental structures. It has been recently demonstrated that accurate stability predictions can also be delivered using modeled protein structures, with AlphaFold2 providing suitable inputs for FoldX even for proteins without homologs in the training set (Akdel et al, 2021; Blaabjerg et al, 2023; Pak & Ivankov, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…AlphaFold2 models were used for proteins or select residues in infrequent cases where they were not covered by experimental structures. It has been recently demonstrated that accurate stability predictions can also be delivered using modeled protein structures, with AlphaFold2 providing suitable inputs for FoldX even for proteins without homologs in the training set (Akdel et al, 2021; Blaabjerg et al, 2023; Pak & Ivankov, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…We tested nine stability predictors, seven of which we have previously also explored for their ability to distinguish between pathogenic and putatively benign human variants (Gerasimavicius et al, 2020). On top of FoldX, Rosetta, INPS3D, PoPMuSiC, mCSM, ENCoM, and DynaMut2, we have included DDGun3D, an “untrained” stability prediction method, as well as the recently released RaSP which offers rapid evaluation of variants based upon sequence alone through a neural network model (Alford et al, 2017; Blaabjerg et al, 2023; Dehouck et al, 2011; Delgado et al, 2019; Frappier et al, 2015; Montanucci et al, 2022; Pires et al, 2014; Rodrigues et al, 2021; Savojardo et al, 2016). While most methods only offer functionality of evaluating stability perturbing effects of mutations on monomeric structures, FoldX, ENCoM and Rosetta were also evaluated in terms of full protein complex structures, if they were available, as this functionality is easily accessible in these predictors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations